Local Maritime Kingdoms in the Nusantara Archipelago (Study of High School Social Studies History Textbook): Kerajaan-Kerajaan Maritim Lokal di Nusantara (Kajian Buku Teks Pelajaran IPS Sejarah SMA) - Nur Syafarudin; Agus Mursidi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The maritime kingdoms in the Nusantara region hold significance in being preserved for future generations through history textbooks as sources and learning media. The challenge lies in how the local maritime kingdoms in Nusantara are presented in the high school history textbooks for Social Studies subjects. The research method employed is qualitative and descriptive, utilizing documents from the 1994, 2006, and 2013 editions of the IPS History textbooks as the data source. Data analysis is conducted by applying Teun A. van Dijk's three dimensions of text, social cognition, and social context theory.The findings reveal that several local maritime kingdoms emphasized in the high school History textbooks are the Kingdoms of Srivijaya, Majapahit, Demak, Samudra Pasai, and Makassar. These kingdoms held strategic positions in maritime regions, with ports serving as trade hubs and transit centers, alongside active community participation in maritime trade activities. A key characteristic of these kingdoms was their strong naval fleets, crucial for maintaining security and order in the sea waters.